Higher expression of CCL2, CCL4, CCL5, CCL21, and CXCL8 chemokines in the skin associated with parasite density in canine visceral leishmaniasis. - Daniel Menezes-Souza; Renata Guerra-Sá; Cláudia Martins Carneiro; Juliana Vitoriano-Souza; Rodolfo Cordeiro Giunchetti; Andréa Teixeira-Carvalho; Denise Silveira-Lemos; Guilherme Corrêa Oliveira; Rodrigo Corrêa-Oliveira; Alexandre Barbosa Reis (Public Library of Science (PLoS), 2012)
BACKGROUND: The immune response in the skin of dogs infected with Leishmania infantum is poorly understood, and limited studies have described the immunopathological profile with regard to distinct levels of tissue parasitism and the clinical progression of canine visceral leishmaniasis (CVL). METHODOLOGY/PRINCIPAL FINDINGS: A detailed analysis of inflammatory cells (neutrophils, eosinophils, mast cells, lymphocytes, and macrophages) as well as the expression of chemokines (CCL2, CCL4, CCL5, CCL13, CCL17, CCL21, CCL24, and CXCL8) was carried out in dermis skin samples from 35 dogs that were naturally infected with L. infantum. The analysis was based on real-time polymerase chain reaction (PCR) in the context of skin parasitism and the clinical status of CVL. We demonstrated increased inflammatory infiltrate composed mainly of mononuclear cells in the skin of animals with severe forms of CVL and high parasite density. Analysis of the inflammatory cell profile of the skin revealed an increase in the number of macrophages and reductions in lymphocytes, eosinophils, and mast cells that correlated with clinical progression of the disease. Additionally, enhanced parasite density was correlated with an increase in macrophages and decreases in eosinophils and mast cells. The chemokine mRNA expression demonstrated that enhanced parasite density was positively correlated with the expression of CCL2, CCL4, CCL5, CCL21, and CXCL8. In contrast, there was a negative correlation between parasite density and CCL24 expression. CONCLUSIONS/SIGNIFICANCE: These findings represent an advance in the knowledge about skin inflammatory infiltrates in CVL and the systemic consequences. Additionally, the findings may contribute to the design of new and more efficient prophylactic tools and immunological therapies against CVL.